(untitled) - Yamamoto, Tsunetomo (Tokyo, 1979)
Outlines the ethical code of the samurai in a time when the martial skills of the warrior became redundant and his role was subsumed into governmental service.
Keywords: Võ Samurai,Samurai; Ứng xử trong cuộc sống,Conduct of life